Необхідність оптимізації інвестиційних грошових потоків підприємств житлово-комунального господарства - Череп, Олександр Григорович (My University, 2014)
У статті розглянуто доцільність забезпечення галузі житлово-комунального господарства інвестиційними ресурсами. Встановлено, що механізми оптимізації грошових потоків саме цієї галузі є недостатньо дослідженими і потребують адаптації до умов та особливостей діяльності підприємств ЖКГ. Обґрунтовано доцільність і необхідність залучення інвестицій у діяльність підприємств комунального господарства. Доведено, що збільшення обсягів бюджетного фінансування підприємств житлово-комунального господарства — це єдине можливе вирішення проблеми збереження існуючих тарифів на житлово-комунальні послуги в умовах постійного зростання цін на імпортовані первинні енергоресурси (газ, нафту). Запропоновано напрями удосконалення фінансування діяльності підприємств комунального господарства в сучасних умовах. In the article expediency of providing of industry of housing and communal services is considered by investment resources. The problem questions of realization of communal reform are investigational. It is set that mechanisms of opti-mization of money streams exactly of this industry are investigational not enough and require adaptation to the terms and features of activity of enterprises of dwelling communal economies. Expediency and necessity of bringing in of investments are reasonable in activity of enterprises of communal economy. It is well-proven that an increase of volumes of the budgetary financing of enterprises of housing and communal services is an only possible decision of problem of maintenance of existent tariffs on dwelling communal services in the conditions of permanent price advance on imported primary resources of energy (gas, oil). Directions of improvement of financing of activity of enterprises of communal economy are offered in modern terms.
Keywords: ресурси; ціна; інвестування; лізинг; resources; price; investment; leasing